(untitled) - Walker, Gordon (Boston, MA., 2004)
Modern Competitive Strategy, by Gordon Walker, provides a highly readable, broad synthesis of the theory and empirics of the strategy field and organizes this material pedagogically for a core strategy course. The approach is eclectic, reflecting the diversity of the discipline. The book draws on studies in industrial and institutional economics, economic and organizational sociology, mainstream strategy, and finance and marketing when appropriate. Both single business and multi-business topics are covered. Many short cases and company examples are used to illustrate the concepts. The material is appropriate for either a full semester course or a single module in MBA programs, advanced undergraduate courses, EMBA and executive education classes.
Keywords: Strategic planning,Industrial management